Contact sensitizer nickel sulfate activates the transcription factors NF-kB and AP-1 and increases the expression of nitric oxide synthase in a skin dendritic cell line - Cruz, MT (2010)
Nuclear factor kappa B (NF-kB) and activating protein-1 (AP-1) transcription factors are ubiquitously expressed signaling molecules known to regulate the transcription of a large number of genes involved in immune responses, namely the inducible isoform of nitric oxide synthase (iNOS). In this study, we demonstrate that a fetal skin-derived dendritic cell line (FSDC) produces nitric oxide (NO) in response to the contact sensitizer nickel sulfate (NiSO(4)) and increases the expression of the iNOS protein, as determined by immunofluorescence and Western blot analysis. The sensitizer NiSO(4) increased cytoplasmic iNOS expression by 31.9 +/- 10.3% and nitrite production, as assayed by the Griess reaction, by 27.6 +/- 9.5%. Electrophoretic mobility shift assay (EMSA), showed that 30 min of FSDC exposure to NiSO(4) activates the transcription factor NF-kB by 58.2 +/- 7.0% and 2 h of FSDC exposure to NiSO(4) activates the transcription factor AP-1 by 26.0 +/- 1.4%. Together, these results indicate that NiSO(4) activates the NF-kB and AP-1 pathways and induces iNOS expression in skin dendritic cells.